The Influence of Electronic Word-of-Mouth and Destination Image on Visit Decision through Visit Intention as Intervening Variable - Aryianto, Muhammad Zaenal; Prihandono, Dorojatun (Management Analysis Journal, 2018)
Now, internet and social media impact on many human life aspects, such as consumer behaviour on traveling in Indonesia. This research aims to exemine the influence of electronic word of mouth and destination image on visit decision. This research also proves the influence of visit intention as an intervening variable. Population are tourists of Panjang Island Jepara. The sampling technique used was purposive sampling technique, the respondents was 116. The data collection method used was questionnaire method. The data analysis used was path analysis. The research variables are electronic word of mouth, destination image, visit decision, and visit intention. Results showed that destination image had a positive and significant influence on visit decision. Meanwhile, electronic word of mouth had no significant influence on visit decision. Results also showed that visit intention had a role as an intervening variable between electronic word of mouth and destination image on visit decision.